Polarizabilities of Pb2+ and Pb4+ and ionization energies of Pb+ and Pb3+ from spectroscopy of high-L Rydberg states of Pb+ and Pb3+ - Hanni, M. E.; Keele, Julie A.; Lundeen, S. R.; Fehrenbach, C. W.; Sturrus, W. G. (My University, 2010)
The binding energies of high-L Rydberg levels of Pb+ with n=19 or 20 and 6⩽L⩽10 were measured with resonant excitation Stark ionization spectroscopy (RESIS). When combined with previous measurements of members of the nh Rydberg series in Pb+, and analyzed with the long-range polarization model, these determined the polarizability of the 5d106s2 ground state of Pb2+ to be αd = 13.62(8) a.u. This value is substantially larger than the estimate published recently based on the measured lifetime of the 6s6p1P1 resonance level of Pb2+, 7.9(6) a.u. The difference is mostly due to the polarizability of Pb4+, the 5d10 core of the Pb2+ ion. This was established by observation of resolved fine structure in the excitation of n=39, high-L Rydberg levels of Pb3+, using the same RESIS technique. Analysis of this spectra determined the polarizability of Pb4+ to be αd = 3.61(4) a.u. Reanalysis of optical spectra of nh and ng levels in Pb+ and Pb3+ in view of the polarizabilities determined in the RESIS studies indicates revised ionization energies of both ions, EI(Pb+) = 121245.28(6) cm−1 and EI(Pb3+) = 341 435.1(8) cm−1.